2002
DOI: 10.2460/javma.2002.220.1177
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver variation among histopathologic evaluations of intestinal tissues from dogs and cats

Abstract: Substantial interobserver variation was detected. Standardization of pathologic descriptions of intestinal tissue is necessary for meaningful comparisons with published articles. Clinicians must be cautious about correlating clinical signs and histopathologic descriptions of intestinal biopsy specimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
143
0
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(151 citation statements)
references
References 21 publications
4
143
0
4
Order By: Relevance
“…Intestinal tissues have been reported to have substantial variation in their histopathologic presentations, as evaluated by pathologists [11]. To our knowledge, there is currently no histopathological criterion for the diagnosis of canine alimentary lymphoma.…”
mentioning
confidence: 99%
“…Intestinal tissues have been reported to have substantial variation in their histopathologic presentations, as evaluated by pathologists [11]. To our knowledge, there is currently no histopathological criterion for the diagnosis of canine alimentary lymphoma.…”
mentioning
confidence: 99%
“…Histopathological analyses of intestinal samples report increased infiltration of the lamina propria of the intestinal mucosa with eosinophils, lymphocytes, plasma cells and (or) neutrophils (German et al, 2001;Craven et al, 2004). However, histopathological reports are variable and do not necessarily correlate with the clinical presentation of the animals (Willard et al, 2002). Based on the combined results of clinical examination, histopathology, responsiveness to treatment and contingent relapses, two main differential diagnoses of CE -food responsive diarrhea (FRD) or inflammatory bowel disease (IBD) -can potentially be distinguished (Willard et al, 2002).…”
mentioning
confidence: 99%
“…However, histopathological reports are variable and do not necessarily correlate with the clinical presentation of the animals (Willard et al, 2002). Based on the combined results of clinical examination, histopathology, responsiveness to treatment and contingent relapses, two main differential diagnoses of CE -food responsive diarrhea (FRD) or inflammatory bowel disease (IBD) -can potentially be distinguished (Willard et al, 2002). However, difficulties in diagnosing FRD or IBD remain and the usefulness for follow-up and prognosis in dogs suffering from CE is questionable.…”
mentioning
confidence: 99%
“…This may have resulted from subtle differences between the biopsy specimens because they were taken from close, but not identical lesions. Moreover, it has been reported that interobserver variation and the quality of endoscopic biopsy specimens influences histopathological outcome [19,20]. Since the endoscopic biopsy specimens were taken by several operators and evaluated by several pathologists, this may have influenced the histopathological diagnoses obtained in the present study.…”
Section: Discussionmentioning
confidence: 65%
“…Lymphocyticplasmacytic inflammation can occur adjacent to or distant from the primary tumor, and distinguishing between alimentary lymphoma and enteritis, especially lymphocytic-plasmacytic enteritis (LPE), can be difficult [4,18]. Additionally, interobserver variation is also an issue in relation to histopathologic evaluation of intestinal tissues [19]. Therefore, full thickness biopsy of the intestine is helpful in making an accurate diagnosis; however, dogs that are suspected of having alimentary lymphoma are usually in poor condition and are unlikely to survive a long period of anesthesia, and laparotomic damage may also occur in some cases.…”
mentioning
confidence: 99%